2012
DOI: 10.1093/ejo/cjs083
|View full text |Cite
|
Sign up to set email alerts
|

Molecular changes in detrained & retrained adult jaw muscle

Abstract: A hypofunctional masticatory system was developed in 21-day-old male rats by feeding them a soft diet for 27 weeks. Retraining of a parallel group for 6 weeks was achieved by switching back to a hard diet after 21 weeks. A control group was fed a hard diet for 27 weeks. At the end of the experimental period, the expression levels of the myosin heavy chain isoform genes MYH 1 and 2 (fast), 3 (embryonic) and 7 (slow) in the deep masseter were compared using qRT-PCR analysis. The gene expressions of MYH 3 and MYH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This is the site of the origin of the deep masseter muscle, which inserts to the lateral surfaces of the body and ramus of the mandible. It was previously found that our rehabilitation model caused an increase of the slow contractile gene expression isoform (MYH 7) levels due to an adaptation to the augmented mechanical load [16].…”
Section: Discussionmentioning
confidence: 87%
“…This is the site of the origin of the deep masseter muscle, which inserts to the lateral surfaces of the body and ramus of the mandible. It was previously found that our rehabilitation model caused an increase of the slow contractile gene expression isoform (MYH 7) levels due to an adaptation to the augmented mechanical load [16].…”
Section: Discussionmentioning
confidence: 87%
“…As previous studies have shown, in the gastrocnemius and soleus muscles, the adult phenotype is determined by an increase in slow-type fibres, which is related to a mature pattern of innervation and physical activity of limb muscles [ 18 ] and is in line with the findings of the current study where an increased Myh7 (MyHC-I) expression was observed in the adult rats compared to the young rats. Similarly, at the level of the masticatory muscles, Odman et al [ 3 ] found that the alteration of the diet from a soft diet to a hard diet (masticatory functional rehabilitation) could trigger a transition of the gene expression isoforms with Myh7 levels increasing as an adaptation to the increased mechanical load.…”
Section: Discussionmentioning
confidence: 99%
“…In order to be able to assess and measure the composition of the masticatory muscles with regard to the different fibre types and their size, animal models are required. In doing so, it has been shown in experimental studies involving an animal model (commonly using a rat model) that changes in the functional demands of the masticatory muscles lead to muscular adaptation, influencing muscle fibre type composition and distribution, fibre diameter and size, as well as total muscle weight [ 3 , 4 ]. The above characteristics may provide the functional profile of the muscle in mature subjects, which seems to be relatively stable, provided that no functional changes occur [ 5 ] and that no pathological disturbances are present [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that changes in diet hardness affect muscular fiber phenotype and enzyme activity encoded by the nuclear and the mitochondrial genome. Moreover, differences in mRNA expression and expression levels of the myosin heavy chain isoform genes MYH 1 and 2 were revealed in experimental rats fed with a soft or hard diet [ 4 ]. Many genes were found to be significantly differentially expressed between hard- and soft-diet-fed mice in groups of the same feeding period.…”
Section: Introductionmentioning
confidence: 99%